PEMAKNAAN MAHKAMAH KONSTITUSI TERHADAP BATASAN OPEN LEGAL POLICY BESERTA KOMPLEKSITASNYA - Muhammad Anugerah Perdana; Mochamad Adli Wafi (Veritas et Justitia, 2025)
The Constitutional Court of Indonesia (Mahkamah Konstitusi) has exhibited a significant shift in its constitutional interpretative practice in adjudicating cases involving open legal policy. This shift is reflected in the Court’s recent tendency to grant judicial review petitions against norms that were previously classified as open legal policy and consistently considered beyond the scope of constitutional review, insofar as such norms are deemed to have exceeded certain constitutional limits. This research employs a normative juridical method and examines two main issues. First, it analyzes how the Constitutional Court conceptualizes the limits of open legal policy in adjudicating and granting judicial review cases. Second, it explores how the complexity of these limits is reflected in the Court’s legal reasoning. The findings indicate that the Constitutional Court has formulated several parameters limiting open legal policy, namely: (1) abuse of power by the legislator; (2) provisions that contravene principles of morality and rationality and result in intolerable injustice; (3) violations of political rights and the principle of popular sovereignty; (4) deficiencies in institutional design and function; and (5) norms that are manifestly contradictory to the 1945 Constitution of the Republic of Indonesia. Nevertheless, this study also reveals various complexities in the application of these limitations, including a tendency toward contradictio in terminis, interpretive difficulties surrounding the concepts of morality, rationality, and intolerable injustice due to their broad and fluid nature, as well as persistent tensions between legal certainty and constitutional justice in judicial review practice.